MECHANICS OF Low TEMPERATURE CRYSTALLIZATION AND RELATED CONSI DERATIONS - uddina, Nayeem; Mahmood, S Naeem; Azmat, Farzana (Biological Sciences - PJSIR, 2002)
Miers theory, although elucidated satisfactorily the phenomenon of supersaturation and consequent crystallization, nevertheless , failed to explain mechanics of POLTEC (processi of low temperature crystallization) in a batch crystal lizer; which has been evolved based on observations made during earlier investigations /logic. It is proposed that because of cooling, the layer in contact with the vessel ’s wall gets supersaturated and is dispersed in solution and spontaneous adiabatic crystallization occurs in each element of dispersed phase . Subsequent to sprouting of salt from each globule, mixing of the liquid residuals causes smooth cooling of solution. Miers idea of required degree of supersaturation , its mechanics and that of POLTEC in context with fluid dynamics/hydrodynamic of batch crystallizer (stirred tank vessel), has been found instrumental in explaining reasons lying behind the pattern of changes in overall heat transfer coefficient and recovery with agitation observed earlier.